2012
DOI: 10.4028/www.scientific.net/amm.174-177.2768
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Delay in Indian Construction Industry

Abstract: Delays in a construction project can be regarded as a failure. This paper aims to investigate the causes of delay in Indian construction projects undertaken by private, government and nongovernmental organizations. In view of this 45 causes of delay were identified and developed the questionnaire for the quantitative confirmation of the most causes of delay. Consequently the questionnaire was distributed to construction professionals like Managers, Engineers and others. Subsequently the collected data was anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Baldwin et al, 1971;Sullivan and Harris, 1986;Walker and Vines, 2000;Chan and Kumaraswamy, 2002). Typical methods used to identify the causes of delays in construction projects include questionnaire survey responses obtained from construction professionals (Koushki et al, 2005) and interviews with practitioners (Venkatesh et al, 2012). Others have reproduced the causes of delays in construction through reviews of the literature (see e.g.…”
Section: Critique Of Prevailing Ideas About Delays In Constructionmentioning
confidence: 99%
“…Baldwin et al, 1971;Sullivan and Harris, 1986;Walker and Vines, 2000;Chan and Kumaraswamy, 2002). Typical methods used to identify the causes of delays in construction projects include questionnaire survey responses obtained from construction professionals (Koushki et al, 2005) and interviews with practitioners (Venkatesh et al, 2012). Others have reproduced the causes of delays in construction through reviews of the literature (see e.g.…”
Section: Critique Of Prevailing Ideas About Delays In Constructionmentioning
confidence: 99%
“…According to Faridi et al (2006), 50% of building projects in the UAE are delayed and not finished on time. To reduce construction delays, Venkatesh et al (2012) suggested improved project management practices that may be used at the project's conceptual and detailed planning stages. Shrivas and Singla (2022) Figure 3 concludes that all the factors selected for the study are relevant because none of the factors falls under the autonomous category.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the five variables, poor monitoring and control were determined to be among the most important of the study's 20 determinants of delay. Similarly, Venkatesh et al (2012) identified poor monitoring of projects as one of the main factors that cause delays. Accidents, poor planning, or a breakdown in communication between the parties can all contribute to mistakes made during the building phase (Lingard et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There are number of studies on the types of delay, its frequency and the causes of delays in construc-tion projects [3][4][5][6][7][8]. There are numerous potential reasons for delay, for example, plan deferrals and lacks, outline changes, variety orders, subcontractor delays, inclement weather conditions, unexpected site conditions and other project delays can be the result of the action/instructions of owners, consultants, contractors or by other external factors to the project.…”
Section: Introductionmentioning
confidence: 99%